KUALITAS PELAYANAN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) PASIEN DIABETES MILITUS DI KLINIK PRIMA MEDIKA SIDOARJO - Ida Susanti; C.Sri Hartati; Gurendro Putro (Prodi Magister Manajemen Universitas Wijaya Putra, 2018)
PENDAHULUAN Sebagai upaya untuk meningkatkan status kesehatan masyarakat serta mensukseskan program jaminan sosial bidang kesehatan, sesuai dengan Peraturan Presiden Nomor 12 Tahun 2013 tentang Jaminan Kesehatan Pasal 21 Ayat 1, maka dilaksanakan Prolanis. Peserta BPJS Kesehatan mendapatkan fasilitas Prolanis yaitu pelayanan kesehatan promotif dan preventif. Prolanis adalah suatu sistem produktivitas masyarakat. Untuk itu BPJS melalui Program pengelolaan penyakit kronis (Prolanis) melakukan upaya promotif dan preventif yang terintegrasi dan model pengelolaan penyakit kronis bagi peserta penderita penyakit kronis, seperti Diabetes Militus. Fenomena tingginya kasus diabetes militus dan hipertensi di Sidoarjo juga dapat dilihat dari kunjungan pasien ke Klinik Prima Medika Sidoarjo. Berdasarkan data Klinik Prima Medika Surabaya, rata-The purpose of this study is to know and analyze the quality of service, efforts to improve the quality of service, obstacles and how to overcome the barriers of service quality in the Program of Management of Chronic Disease (Prolanis) diabetes mellitus patients in Prima Medika Clinic Sidoarjo. This research is a qualitative research to analyze service quality in Chronic Disease Management Program (Prolanis) of diabetes mellitus patient in Prima Medika Clinic Sidoarjo. Primary data were obtained from in-depth interviews of patients, doctors, nurses, administrators, and BPJS officers. The results showed that the Prima Medika Clinic in Sidoarjo already has a good service quality in organizing the Prolanis of diabetes mellitus patients. The clinic's efforts in improving the quality of proline services is by providing medical consultation, education / counseling, reminder via SMS / phone, home visite for participants who are not coming 3 times, Prolanis gymnastics, health monitoring. As for Prolanis obstacles that some Prolanis participants are often absent in Prolanis activities, diabetics do not nurse maximally, lack of coordination and cooperation between faskes 1 and faskes 2. To overcome barriers, home visits from Prolanis participants are frequent not present in activities to find out the cause, integrated data update about people affected by diabetes mellitus disease, increased cooperation between faskes 1 and 2. Keywords: service quality, chronic disease management program